2022
DOI: 10.3889/oamjms.2022.8179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Channa striata Extract on Albumin Serum and Neutrophil-to-Lymphocyte Ratio in Hyperglycemic Rats with Wound Injury: A Randomized Control Study

Abstract: BACKGROUND: Patients with hyperglycemia often experience slow wound healing due to poor circulation. Extract from the striped snakehead fish Channa striata has anti-inflammatory properties and a high albumin level. It has been widely used to accelerate wound healing in a post-operative setting. AIM: This study evaluated the effect of the C. striata extract Pujimin Plus® on the albumin serum level and neutrophil-to-lymphocyte ratio (NLR) in hyperglycemic rats experiencing wound injury. METHODS: This randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Vitamin D receptor also involved in calcium signaling and myogenesis (19,20). Serum vitamin D levels increase after given oral vitamin D(21,22) In this study showed increases serum vitamin D level serum signi cantly after 4 and 8 weeks supplementation compared to the control group. Production of vitamin D can decrease caused by genetic, dark skin color, sunscreen, and limited sunlight exposure, or when cutaneous vitamin D synthesis decrease (19,23,24).…”
mentioning
confidence: 49%
“…Vitamin D receptor also involved in calcium signaling and myogenesis (19,20). Serum vitamin D levels increase after given oral vitamin D(21,22) In this study showed increases serum vitamin D level serum signi cantly after 4 and 8 weeks supplementation compared to the control group. Production of vitamin D can decrease caused by genetic, dark skin color, sunscreen, and limited sunlight exposure, or when cutaneous vitamin D synthesis decrease (19,23,24).…”
mentioning
confidence: 49%
“…In addition, C. striata is used as a postoperative wound medicine, malaria medicine, and typhus (Syafutra et al 2021). The species has anti-inflammatory properties and high albumin levels, so it has been widely used to accelerate postoperative wound healing (Taslim et al 2022). In addition, C. striata has antimicrobial and antinociceptive effects (Sahid et al 2018;Ma'rufi et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The content of compounds in snakehead fish acts as an anti-inflammatory effect that can increase albumin levels and reduce the number of neutrophils in hypoalbuminemia who are injured. Taslim et al (2022) research on hyperglycemic rats with wounds showed that the intervention group on day 10 experienced a decrease in neutrophils and an increase in albumin and lymphocyte values. A decrease in the percentage of neutrophils occurs when there is a decrease in the signal from the proinflammatory sticonyl-17 that suppresses its production in the bone marrow.…”
Section: Effect Of Giving Snakehead Fish Extract (Channa Striata) On ...mentioning
confidence: 99%